2016
DOI: 10.1091/mbc.e15-10-0699
|View full text |Cite
|
Sign up to set email alerts
|

The far C-terminus of MCAK regulates its conformation and spindle pole focusing

Abstract: Spatial regulation of microtubule dynamics is critical for proper spindle assembly. The far C-terminus of the microtubule-depolymerizing kinesin-13 MCAK regulates MCAK localization at spindle poles, which is needed for proper pole focusing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 46 publications
5
20
0
Order By: Relevance
“…Specifically, it is possible that the addition of a second MT-binding domain might alter the quaternary structure of the probe (as compared with SH-TSmod), locking it in a conformation that adversely affects binding to MTs within the spindle midzone. The change in localization resulting from the addition of a second mTMBD is conceptually similar to the different localization patterns observed for different conformations of kinesin-13 in Xenopus egg extract spindles (Zong et al 2016). …”
Section: Discussionsupporting
confidence: 61%
“…Specifically, it is possible that the addition of a second MT-binding domain might alter the quaternary structure of the probe (as compared with SH-TSmod), locking it in a conformation that adversely affects binding to MTs within the spindle midzone. The change in localization resulting from the addition of a second mTMBD is conceptually similar to the different localization patterns observed for different conformations of kinesin-13 in Xenopus egg extract spindles (Zong et al 2016). …”
Section: Discussionsupporting
confidence: 61%
“…Two recent studies showed that GTSE1 localizes to the spindle during mitosis, and like TACC3, is necessary for astral microtubule stabilization and efficient chromosome alignment (Bendre et al, 2016;Tipton et al, 2017). We showed that GTSE1 stabilizes MTs in mitosis by inhibiting MCAK activity (Bendre et al, 2016). In that study, cancer cells either depleted or knocked-out of GTSE1 showed destabilization of both astral MTs and kinetochore-MT attachments.Another study reported that a specific "slow turnover" population of MTs become stabilized upon depletion of GTSE1(Tipton et al, 2017).…”
mentioning
confidence: 58%
“…However, whether clathrin (or the CHC/TACC3 complex) is required for astral microtubule stabilization has not been addressed.Another potential functional member of the CHC/TACC3 complex is GTSE1 (pronounced "jitsee-one" (Monte et al, 2000)), an intrinsically disordered protein that has been shown by proteomic analysis to interact with the CHC/TACC3 complex in cells (Hubner et al, 2010). Two recent studies showed that GTSE1 localizes to the spindle during mitosis, and like TACC3, is necessary for astral microtubule stabilization and efficient chromosome alignment (Bendre et al, 2016;Tipton et al, 2017). We showed that GTSE1 stabilizes MTs in mitosis by inhibiting MCAK activity (Bendre et al, 2016).…”
mentioning
confidence: 77%
See 2 more Smart Citations